(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In recent years, digital financial services have been a major driver of financial inclusion. While there is evidence that traditional financial inclusion has a positive impact on economic growth. Any country's economic development is built on the foundation of digital financial services. Mobile banking and mobile money are two new concepts that are transforming bulk services into personalised services. This has resulted in the creation of digital financial inclusion, which fosters efficient interconnection among participants in economic activity. When a poor, previously unbanked consumer begins to transact digitally with his or her family and friends, formal banking and financial institutions, and utility companies, it is called a success. This paper attempts to identify the preliminary concepts of digital financial inclusion, status in India and Tumakuru District and reasons for digital financial exclusions.